Successful Combined Treatment of a Patient with Borderline Resectable Liver Metastasis of Colorectal Cancer - O. Yu. Stukalova; A. A. Polikarpov; A. V. Moiseenko; D. A. Granov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present the value of interventional radiology techniques in the treatment of a patient with liver metastasis of colorectal cancer.Key points. In 2013, a 60-year-old patient with stage IIIB sigmoid colon cancer, pT3N2M0 underwent resection of the sigmoid colon with the formation of hardware rectosigmoanastomosis, 6 courses of adjuvant chemotherapy were performed. In 2015, a control examination revealed metastatic liver damage. Liver resection could not be performed due to the small future residual volume, and systemic chemotherapy was not effective. The patient underwent 3 cycles of regional chemotherapy. Taking into account the pronounced positive dynamics, in the form of a decrease in tumor size and a decrease in cancer markers, the patient managed to perform an extended right-sided hemihepatectomy. No progression of the tumor process was detected during the follow-up.Conclusion. Modern possibilities of X-ray endovascular methods allow to achieve results in the treatment of patients with colorectal cancer metastases in the liver such as a decrease in metastases in size, that make liver resection possible.